Electrochemical Behavior of Screen-Printed Carbon Electrodes as Transducers in Biosensors - Dorledo de Faria, Ricardo Adriano; Douaud, Alexandre; Soares, Renata Braga; Dias Heneine, Luiz Guilherme; Matencio, Tulio; Cunha Lins, Vanessa de Freitas; Messaddeq, Younes [UNESP] (Natl Assoc Corrosion Eng, 2020)
Screen-printed carbon electrode (SPCE) was examined as a transducer substrate for application in electrochemical sensors. Aqueous solutions of 0.1 M KCl and 0.1 M KCl + 5 mM K-3[Fe(CN)(6)]/K-4[Fe(CN)(6)] (redox solution) were prepared to simulate the environment of faradaic and non-faradaic sensing, respectively. The SPCE presented an irregular surface composed by two main carbon phases. Raman spectroscopy results revealed the presence of peaks around 1,580 cm(-1) and 1,334 cm(-1) related to the G and D bands corresponding to sp(2) carbon atoms (graphite flakes) and a multitude of broad bands associable to amorphous sp(3) carbon in the ink matrix. Conductive atomic force microscopy indicated that the irregular structure of the SPCE led to the heterogeneous distribution of the current over the surface and the electroactivity of this material was mainly attributed to the presence of graphite. Polarization curves and electrochemical impedance spectroscopy (EIS) revealed that the redox solution was more aggressive to the SPCE, despite this electrode was achieved a quasi-steady state for 1 h under the effect of a polarization potential in both electrolytes, which justifies its use as an electrochemical transducer in faradaic and non-faradaic devices.
Keywords: corrosion; faradaic electrochemical impedance spectroscopy (EIS); non-faradaic electrochemical impedance spectroscopy (EIS); screen-printed carbon electrode; sensor